When missing NPs make double center-embedding sentences acceptable. Issue 1 (6th April 2021) - Huang, Nick; Phillips, Colin
Abstract : A number of languages, such as English, exhibit a grammaticality illusion in ungrammatical double center-embedding sentences where a VP is missing. This article shows that the illusion generalizes to ungrammatical Mandarin Chinese double center-embedding sentences where the head NP of a relative clause is missing. The Mandarin illusion raises interesting questions for existing accounts of center-embedding illusions. Mandarin missing NP sentences consist of three transitive verbs and only three NPs; the clear shortage of NPs should affect the thematic relations built for such sentences, with potential consequences for acceptability. We explore these issues with acceptability judgment experiments. We show that these illusory sentences receive distinct thematic interpretations compared to their better-studied missing VP counterparts, in ways not predicted by structural forgetting or interference accounts. A computational simulation further shows that the Mandarin illusion is problematic for accounts that attribute cross-linguistic variation in the illusion to differences in language experience. To capture cross-linguistic variation, we build on existing interference accounts, in which the parser mis-attaches a verb or NP to the main clause instead of a relative clause. We supplement this approach with a repair process, in which the parser tracks thematic relations, repairing them where necessary so no verb or noun is thematically "orphaned." We suggest that the illusion of grammaticality arises when the parser can establish thematic relations between all verbs and nouns. This interference-and-repair approach provides a unified analysis of the missing VP and missing NP illusions, while accounting for the observed difference in thematic relations.